Design and Performance Analysis of Photovoltaic Solar Cells Using WSe2 as an Absorber Layer with SnS2 Electron Transport Layer - Paul, Indrojit; Rayhan, Abu; Khan, M. A. (New Energy Exploitation and Application, 2025)
Recent breakthroughs in solar cell technology have highlighted transition metal dichalcogenides, particularly tungsten diselenide (WSe₂), as exceptional absorber materials due to their remarkable optoelectronic properties. This study presents an innovative thin-film photovoltaic solar cell featuring Cu₂O-WSe₂-SnS₂ layers. Utilizing WSe₂ as the primary absorber, SnS₂ as the electron transport layer (ETL), and Cu₂O as the hole transport layer (HTL), this structure is engineered to maximize light absorption and carrier separation, enhancing energy efficiency. Key performance parameters, including power conversion efficiency (PCE), fill factor (FF), short-circuit current density (Jsc), and open-circuit voltage (Voc), were thoroughly evaluated. The impressive results—PCE of 25.76%, FF of 83.36%, Voc of 1.29 V, and Jsc of 23.84 mA/cm²—were achieved through meticulous simulation and experimental validation. Investigating defect densities at the SnS₂/WSe₂ and WSe₂/Cu₂O interfaces revealed that minimizing interfacial recombination significantly enhances charge extraction and overall performance. A comparative analysis confirmed SnS₂ as an optimal ETL due to superior electron mobility and minimal recombination. This optimized structure offers excellent efficiency and operational stability, providing crucial insights into the feasibility of WSe₂-based thin-film solar cells. Additionally, it advances our understanding of interfacial engineering in photovoltaics and underscores the role of WSe₂ in conjunction with Cu₂O and SnS₂. These findings contribute to ongoing research on high-efficiency thin-film solar cells, paving the way for further innovations in solar energy conversion technology.